Ridge Till Flood-Irrigated Corn - Sartwelle III, James D.; Henson, Darl W. (My University, 1995)
This publication provides expected yields and enterprise return for producing flood-irrigated corn under a ridge-till cropping system.
MF969_1995_10
Keywords: MF969; Economics; Crops; MF